Prognostic Value of Preoperative CEA and CA 19-9 Levels in Patients with Colorectal Cancer - Basbug, Murat; Arikanoglu, Zulfu; Bulbuller, Nurullah; Cetinkaya, Ziya; Aygen, Erhan; Akbulut, Sami; Satici, Omer (H G E Update Medical Publishing S A, 2011)
Aims: This study evaluated the prognostic value of the preoperative CEA and CA 19-9 levels on the survival time and TNM staging in patients with colorectal cancer. Methodology: We retrospectively analyzed 172 patients who underwent potentially curative resection of colorectal cancer (TNM I-III) between 2002 and 2007. Clinical data were obtained from medical charts, including age, gender, tumor location, TNM stage, mortality, follow-up duration, and preoperative CEA and CA 19-9 levels. A CEA >= 5ng/mL was defined as abnormal (CEA+), while the cutoff for the CA19-9 was set at 37U/mL (CA19-9+). Patients were categorized into Groups I-IV according to the preoperative serum CEA and CA 19-9 levels [CEA/CA 19-9: (-/-), (+/-), (-/+), and (+/+)]. Results: Follow-up was longest for Group I (p<0.001). Mortality rates were higher in Groups V' (p<0.001) and II (p<0.008). On comparing patients according to CEA levels, survival was longer in the CEA-negative group (p=0.0001). On comparison according to CA 19-9 levels, survival was greater in the CA 19-9-negative group (p=0.0001). While CEA (p<0.016) and CA 19-9 (p<0.001) were independent prognostic factors according to the logistic regression analysis, TNM (p=0.002), CEA (p<0.001), and CA 19-9 (p<0.001) were prognostic factors in the ROC curve analysis. Conclusions: Colorectal cancer patients with elevated levels of both CEA and CA 19-9 have a significantly poorer prognosis than those with normal levels of these tumor markers.
Keywords: Colorectal cancer; Carcinoembryonic antigen (CEA); Carbohydrate antigen 19-9 (CA 19-9)